A holistic approach to understanding the iron-gall inks in the historical documents of the Portuguese Inquisition (1570–1790). (February 2023) - Nunes, Margarida; Olival, Fernanda; Mitchell, Scott G.; Claro, Ana; Ferreira, Teresa
Abstract: A substantial part of our written heritage is threatened by the fact that much of it has been written using iron-gall ink (IGI). One such example is the documents of the Portuguese Inquisition Tribunals, held by the Arquivo Nacional da Torre do Tombo. Here we present the first systematic analytical approach, using SEM/EDS, µ-FT-IR-ATR and µ-Raman techniques, to characterise fragments from historical records of the Inquisition Tribunals of Évora, Lisboa and Coimbra from the 16th to 18th centuries. The writing ink was identified as IGI, providing complementary compositional data and establishing differences between various formulations of the ink. Additionally, the deleterious effects of the inks-associated degradation phenomena were highlighted. This work allowed understand the writing inks used by this Portuguese institution. Highlights: The first insight into the composition of the writing inks used by the Portuguese Inquisition (1590–1790). The combined use of SEM-EDS, FT-IR and Raman techniques allowed us to distinguish iron-gall inks' formulations. 3D digital microscopy highlighted the presence of sediments as powder and micro-sized crystal particles in the inked areas. This work supports the hypothesis of an established trade for ink acquisition or centralised ink production.